2017
DOI: 10.3389/fphys.2017.00495
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability: A Novel Modality for Diagnosing Neuropathic Pain after Spinal Cord Injury

Abstract: Background: Heart rate variability (HRV), the physiological variance in the heart's R-R interval length, can be analyzed to produce various parameters reflective of one's autonomic balance. HRV analysis may be used to capture those autonomic aberrations associated with chronic neuropathic pain (NP) in spinal cord injury (SCI). This study assesses the capacity of HRV parameters to diagnose NP in an SCI cohort.Methods: An electrocardiogram (ECG) was collected at rest from able bodied participants (AB, n = 15), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…We recently published an innovative study that evidenced the capacity of baseline HRV parameters, namely time domain variables, to differentiate chronic SCI subjects with and without NP. 24 Additionally, we demonstrated that those HRV differences were unlikely to be influenced by the neurologic level or severity of the SCI itself. 24 …”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We recently published an innovative study that evidenced the capacity of baseline HRV parameters, namely time domain variables, to differentiate chronic SCI subjects with and without NP. 24 Additionally, we demonstrated that those HRV differences were unlikely to be influenced by the neurologic level or severity of the SCI itself. 24 …”
Section: Introductionmentioning
confidence: 69%
“… 24 Additionally, we demonstrated that those HRV differences were unlikely to be influenced by the neurologic level or severity of the SCI itself. 24 …”
Section: Introductionmentioning
confidence: 69%
“…Many studies within chronic pain have found decreased SDNN within clinical populations compared to healthy controls (12) and HRV suppression has been correlated with pain severity or disability perception (59,65,66). One study (67) measured SDNN in patients with spinal cord injury (SCI) with and without neuropathic pain and found significant lower resting SDNN in SCI patients with pain compared to SCI without pain and healthy controls. Since SDNN includes input from both the parasympathetic and sympathetic input, few conclusions on the increase of specific ANS branches can be drawn (12), but SDNN has been hypothesized to provide objective quantification of analgesic response to pain treatment (67).…”
Section: Discussionmentioning
confidence: 99%
“…One study (67) measured SDNN in patients with spinal cord injury (SCI) with and without neuropathic pain and found significant lower resting SDNN in SCI patients with pain compared to SCI without pain and healthy controls. Since SDNN includes input from both the parasympathetic and sympathetic input, few conclusions on the increase of specific ANS branches can be drawn (12), but SDNN has been hypothesized to provide objective quantification of analgesic response to pain treatment (67). Therefore, increasing overall HRV (SDNN) may be beneficial in patients with CLBP, and HRV intervention studies have shown increases in total HRV (24).…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain after SCI is probably due to maladaptive plastic cortical reorganization and sensitization of the central nervous system (CNS), although this is poorly understood (3,(47)(48)(49)(50). As a result of SCI and partial/complete denervation of spinal neurones, communication between the brain and the periphery is partially or completely interrupted.…”
Section: Comparisons Between Tdcs and Breestimmentioning
confidence: 99%